(untitled) (AmS-Skrifter, 2019)
Liminalities and ambiguities can be useful in identifying complex patterns in many areas of study. This paper examines two elderly burials from the Anglo-Saxon cemetery of Mill Hill, Deal, Kent in England. These two individuals display multiple liminalities, particularly with respect to their advanced age, gendered identities and in their potential religious beliefs. Their advanced age suggests they spent the last years of their lives in the knowledge that they were close to the ultimate transition: death. Moreover, being quite elderly has likely affected their gendered identities, rendering them muted, altered and/or de-gendered. The combination of their elderly status, their physical position in the cemetery and the phasing of their graves suggests they were the last two individuals buried at Mill Hill, possibly some considerable time after it had gone out of general use. Their graves are dated to the Final Phase or Conversion Period of Early Anglo-Saxon England when, among other changes, Christianity begins to become the dominant religion; this and the presence of an unexcavated cemetery nearby, with goods pointing to a later date than this one, suggests the possibility that these two individuals were the last pagans in their community. These are all factors which point to the multiple liminalities of the two individuals.